1998
DOI: 10.1128/jvi.72.6.4775-4782.1998
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interaction of Eukaryotic Translation Initiation Factor 3 with the 5′ Nontranslated Regions of Hepatitis C Virus and Classical Swine Fever Virus RNAs

Abstract: Translation of hepatitis C virus (HCV) and classical swine fever virus (CSFV) RNAs is initiated by cap-independent attachment (internal entry) of ribosomes to the ∼350-nucleotide internal ribosomal entry segment (IRES) at the 5′ end of both RNAs. Eukaryotic initiation factor 3 (eIF3) binds specifically to HCV and CSFV IRESs and plays an essential role in the initiation process on them. Here we report the results of chemical and enzymatic footprinting analyses of binary eIF3-IRES complexes, which have been used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(108 citation statements)
references
References 31 publications
8
99
0
1
Order By: Relevance
“…Previously, a IIIb position much closer to the 40S subunit and overlapping with the IIIabc four-way junction in our present model was suggested (Boehringer et al, 2005;Siridechadilok et al, 2005). Because IIIb interacts with the eIF3 initiation factor complex (Sizova et al, 1998;Ji et al, 2004;Otto & Puglisi, 2004), our model places this major eIF3 binding site further away from the ribosome in excellent agreement with the direct visualization of eIF3 on the related 40S-bound CSFV IRES with a deletion of domain II (Hashem et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Previously, a IIIb position much closer to the 40S subunit and overlapping with the IIIabc four-way junction in our present model was suggested (Boehringer et al, 2005;Siridechadilok et al, 2005). Because IIIb interacts with the eIF3 initiation factor complex (Sizova et al, 1998;Ji et al, 2004;Otto & Puglisi, 2004), our model places this major eIF3 binding site further away from the ribosome in excellent agreement with the direct visualization of eIF3 on the related 40S-bound CSFV IRES with a deletion of domain II (Hashem et al, 2013).…”
Section: Discussionsupporting
confidence: 87%
“…The class III IRES in HCV and pestivirus RNAs uses a prokaryote-like mode of translation initiation by positioning ribosomes on the mRNA through interactions with both eIF3 and the ribosome itself, thereby circumventing any need for eIF4F Sizova et al 1998;Ji et al 2004;Otto and Puglisi 2004;Pisarev et al 2004;Fraser and Doudna 2007;Locker et al 2007;Babaylova et al 2009;Berry et al 2010). Translation of HCV RNA is also enhanced by the binding of host miR-122 to two target sites in the 5 0 UTR, thereby promoting ribosome recruitment (Jopling et al 2005(Jopling et al , 2008Henke et al 2008;Jangra et al 2010).…”
Section: Translation Mediated By Class III and Iv Iresmentioning
confidence: 99%
“…[15][16][17] The IRES activity is highly dependent on both the primary sequence of this segment and its ability to form complex secondary and tertiary RNA structures. [18][19][20][21][22] A number of in vitro studies have suggested that several cellular proteins, including both conventional translation initiation factors such as eukaryotic initiation factor 3 (eIF3) 23,24 and noncanonical translation initiation factors such as the nuclear La protein [25][26][27][28][29] or polypyrimidine tract binding protein (PTB), [30][31][32] may stimulate HCV translation. We previously reported that HCV translation is regulated in a cell-cycle-dependent manner and that cellular proteins that vary in abundance during the cell cycle may be involved in this process, 33 but to date, the mechanism by which HCV translation is regulated in vivo is not well understood.…”
mentioning
confidence: 99%